Long-term prognostic impact of the left anterior descending coronary artery as the STEMI-related culprit vessel: subanalysis of the EXAMINATION-EXTEND trial - Pablo Vidal-Calés; Kamil Bujak; Riccardo Rinaldi; Anthony Salazar-Rodríguez; Luis Ortega-Paz; Josep Gómez-Lara; Víctor Jiménez-Díaz; Marcelo Jiménez; Pilar Jiménez-Quevedo; Roberto Diletti; Pascual Bordes; Gianluca Campo; et al. (REC: Interventional Cardiology (English Ed.))
ABSTRACT Introduction and objectives: There is limited data on the impact of the culprit vessel on very long-term outcomes after ST-elevation myocardial infarction (STEMI). The aim was to analyze the impact of the left anterior descending coronary artery (LAD) as the culprit vessel of STEMI on very long-term outcomes. Methods: We analyzed patients included in the EXAMINATION-EXTEND study (NCT04462315) treated with everolimus-eluting stents or bare-metal stents after STEMI (1498 patients) and stratified according to the culprit vessel (LAD vs other vessels). The primary endpoint was the patient-oriented composite endpoint (POCE), including all-cause mortality, myocardial infarction (MI) or revascularization at 10 years. Secondary endpoints were individual components of POCE, device-oriented composite endpoint and its individual components and stent thrombosis. We performed landmark analyses at 1 and 5 years. All endpoints were adjusted with multivariable Cox regression models. Results: The LAD was the culprit vessel in 631 (42%) out of 1498 patients. The LAD-STEMI group had more smokers, advanced Killip class and worse left ventricular ejection fraction. Conversely, non-LAD-STEMI group showed more peripheral vascular disease, previous MI, or previous PCI. At 10 years, no differences were observed between groups regarding POCE (34.9% vs 35.4%; adjusted hazard ratio [HR], 0.95; 95% confidence interval [95%CI], 0.79-1.13; P = .56) or other endpoints. The all-cause mortality rate was higher in the LAD-STEMI group (P = .041) at 1-year. Conclusions: In a contemporary cohort of STEMI patients, there were no differences in POCE between LAD as the STEMI-related culprit vessel and other vessels at 10 years follow-up. However, all-cause mortality was more common in the LAD-STEMI group within the first year after STEMI.